Analysis of Market Positioning and Brand Competitiveness of Starbucks and Luckin Coffee in China - Jiang Mingjue (SHS Web of Conferences)
This paper analyses the positioning and brand competitiveness of Starbucks and Luckin Coffee in the Chinese market. It begins by outlining the current situation of the Chinese coffee market and discussing consumer behavior and market trends. The growing preference for coffee culture among young, urban consumers significantly drives market demand in China. Starbucks and Luckin Coffee hold prominent positions, catering to distinct customer segments. This paper examines the brand positioning of Starbucks and Luckin and their target segments, revealing that Starbucks attracts mid-to-high-end consumers through its premium image. At the same time, Luckin wins over the young and busy urban segment with its convenience and value for money. The study also compares their product and service differentiation and analyses the differences in their digital strategies. Starbucks focuses on the offline experience and is committed to creating a ‘third space’ with a warm and friendly atmosphere, while Luckin relies on the mobile internet and is data-driven to realize coffee at one’s fingertips. The paper concludes by summarising each brand’s strengths and identifying opportunities for enhanced competitiveness.